A Novel Imidazo[1,5-b]isoquinolinone Derivative, U63A05, Inhibits Syk Activation in Mast Cells to Suppress IgE-Mediated Anaphylaxis in Mice - Do Kyun Kim; Jun Ho Lee; Jie Wan Kim; Hyuk Soon Kim; A-Ram Kim; Bo Kyung Kim; Kyu Yang Yi; Hye-Jin Park; Dong Ki Park; Wahn Soo Choi (Elsevier, 2011)
Mast cells play a pivotal role in IgE-mediated allergic responses. Development of specific inhibitors against FcεRI-associated proximal signaling molecules in mast cells may represent a promising therapeutic strategy for allergic diseases. We examined whether a novel synthetic compound, 3-butyl-1-chloro-8-(2-methoxycarbonyl)phenyl-5H-imidazo[1,5-b]isoquinolin-10-one (U63A05), could suppress antigen-stimulated degranulation and cytokine secretion in mast cells and IgE-mediated passive cutaneous anaphylaxis (PCA) in mice. U63A05 reversibly and dose-dependently inhibited degranulation of rat basophilic leukemia (RBL)-2H3 mast cells and bone marrow-derived mast cells (BMMCs) stimulated by antigen (IC50 values for RBL-2H3 and BMMCs were 4.1 and 4.8 μM, respectively). The secretion of inflammatory cytokines was also suppressed in antigen-stimulated mast cells. However, degranulation by thapsigargin, a typical calcium inducer, was not inhibited by U63A05. U63A05 exerts its inhibitory effect, to the same extent as in degranulation, on the activating phosphorylation of Syk and downstream signaling molecules, including LAT and SLP-76. Further downstream, the activating phosphorylations of Akt, Erk1/2, p38, and JNK were also inhibited. Finally, antigen-stimulated PCA was dose-dependently suppressed in mice (ED50, 26.3 mg/kg). Taken together, the results suggest that U63A05 suppresses the activation of mast cells and the mast cell-mediated allergic response through the inhibition of Syk activation in mast cells. Keywords:: 3-butyl-1-chloro-8-(2-methoxycarbonyl)phenyl-5H-imidazo[1,5-b]isoquinolin-10-one (U63A05), mast cell, IgE, type I hypersensitive response, syk